Intrapancreatic accessory spleens in African swine fever infection of wild boar (Sus scrofa) - Porras, Néstor; Chinchilla, Blanca; Rodríguez-Bertos, Antonio; Barasona, José Á.; Kosowska, Aleksandra; Vázquez-Fernández, Esther; Sánchez-Cordón, Pedro J.; Sánchez-Vizcaíno, José M. (Frontiers in Veterinary Science, 2023)
Intrapancreatic accessory spleen (IPAS) is one of the most frequent congenital splenic anomalies in humans; however, studies in veterinary medicine are scarce. This study aimed to describe the macroscopic, histopathological and immunohistochemical features of eleven suspected cases of IPAS in wild boar piglets of 3-4 months old. Seven of the eleven animals were immunised with a low virulence isolate of African swine fever virus (ASFV) and subsequently challenged with a highly virulent ASFV isolate (LVI-HVI group). The remaining four animals were exclusively infected with a highly virulent isolate of ASFV (HVI group). Grossly, lesions comprised focal or multifocal reddish areas of variable shape, located on the surface of the pancreatic tail or within the parenchyma. Histological and immunohistochemical studies (anti-CD79 and CD3) confirmed the presence of IPAS in eight of the eleven cases. IPAS shared the same histological structure and alterations as those observed in the original spleen. The immunohistochemical study against ASFV revealed the presence of VP72+ cells in both the spleen and IPAS of seven of the eight piglets. The results of this study describe for the first time the presence of IPAS in ASFV infection of wild boar (Sus scrofa) regardless the isolate and suggest that the infection may induce the development of ectopic splenic tissue due to an increased demand for phagocytic cells from the reticuloendothelial system. However, further studies are needed to understand the immunological mechanisms that trigger the formation of these accessory organs.